خصوصيات لغة التواصل عند عبد القاهر الجرجاني من خلال كتابيه "دلائل الإعجاز" و"أسرار البلاغة" - قابوسة, زبيدة; حرزولي, العزوزي (University of El-oued, 2021)
اهتم علماء اللغة منذ الزمن البعيد بالتواصل وعناصره وطرق نجاحه وأيضا بشروطه اللغوية، وغير اللغوية التي تعد من أساسيات الدرس التداولي حديثا، والبلاغي قديما الذي من بين رواده الإمام عبد القاهر الجرجاني، كونه اهتم باللغة أثناء الاستعمال لا بعزلها عنه كبنية مجردة من خصوصيات مميزة من شأنها إذا توفرت في اللغة أهلت المتخاطبين لنجاح عمليتي الفهم والإفهام ومنه إلى نجاح العملية التواصل بصفة عامة. ففي هذه الورقة البحثية سنحاول الوقوف على بعض أسس التواصل اللسانية منها وغير اللسانية التي اعتمدها إمام البلاغة من خلال تحليلاته التداولية لمجموعة خصوصيات ومعايير تواصلية في كتابيه "دلائل الإعجاز" و"أسرار البلاغة" وسنعتمد في ذلك خطة مناسبة تمثلت في: مقدمة، وعرض تضمّن خصوصيات لغة التواصل، وخاتمة Linguists have long been concerned with communication, its elements and methods of success, as well as its linguistic and non-linguistic terms, which are among the basics of the modern pragmatic lesson, and the rhetoric in the past. Abdelkader al-Jaurjani was one of the pioneers because he was interested in language in use not by isolating it from it as an abstract structure of distinctive features If the language is present, it will qualify the interlocutor for the success of the process of understanding and being understood, and from it to the success of the process of communication in general. In this research paper, we will attempt to focus on some of the linguistic and non-linguistic foundations of communication that Imam al-Balagha adopted through his deliberative analyzes of a set of communicative peculiarities and criteria in his books “Evidence of Miracles” and “Secrets of Rhetoric”. They adopted an outline plan in that: an introduction, a presentation that included the specifics of the language of communication, and a conclusion
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج04. ع.02. جامعة الوادي
Keywords: التداولية ; التواصل ; الاستعمال ; المتخاطبين ; القصد ; التأويل